A morphologist, a modeler, and an endocrinologist consider sea turtle sex ratios in a changing climate. Some wine was involved - Heppell, Selina S.; Wyneken, Jeanette; Heppell, Scott A. (Frontiers in Ecology and Evolution, 2022)
Because the sex of sea turtles is determined by temperature during embryonic development, many populations are vulnerable to increased bias in primary sex ratios as global temperatures rise. Higher temperatures produce more females, and some populations are already showing years with all-female offspring production. But because sea turtles take decades to mature and have long adult lifespans, these primary sex ratio biases can take years to impact adult sex ratios, and the males from cohorts that are produced during cooler years may compensate for the sex ratio bias if they can breed more frequently and with multiple females. To date, little is known about male sea turtle reproductive behavior, making predictions of sex ratio skew impacts highly speculative. We used data from southern Florida loggerhead sea turtle nests to parameterize a simple population model to explore the effects of an increase in the proportion of female hatchlings over time on population trends, effective population size (Ne), and quasi-extinction probability. We also tested the effects of increasing the frequency of relatively high male production years to simulate potential mitigation strategies. While heuristic rather than predictive, our results expectedly show a rise in nest counts due to the increase in females over time, followed by population decline as males become limiting. Population collapse due to increased female bias will take many decades to occur, but sex ratio skew can have large impacts on Ne, and thus increase the potential for inbreeding. An increase in the frequency of male production years, even just one additional “good male year” per decade, can help mitigate these outcomes if the rate of feminization is not too rapid. Male breeding frequency and mating success are critical drivers of the results and must be prioritized for research.